Cryopreservation of equine embryos with glycerol plus sucrose and glycerol plus 1,2-propanediol. - Ferreira, J. C.; Meira, Cezinande de [UNESP]; Papa, Frederico Ozanam [UNESP]; Landim-Alvarenga, Fernanda da Cruz [UNESP]; Alvarenga, Marco Antonio [UNESP]; Buratini, J. (Wiley, 1997)
Six or 7-day-old equine embryos were divided into 4 groups; Group 1, n = 15, Day 7 embryos destined for immediate transfer; Group 2, n = 15, Day 6 embryos destined for deep-freezing with glycerol plus sucrose as cryoprotectant; Group 3, n = 10, Day 6 embryos destined for deep-freezing with glycerol plus 1,2-propanediol as cryoprotectant and Group 4, n = 3, fresh embryos destined for ultrastructural analysis. All the frozen/thawed embryos were transferred to recipient mares, except 3 embryos in Group 3 that were subjected to ultrastructural analysis. After thawing the cryoprotectants were removed by successive dilutions in PBS + 15% v:v fetal calf serum (FCS) containing decreasing concentrations of the cryoprotectants. Pregnancy was diagnosed ultrasonographically in 53.3%, 13.3% and 0% of the mares in Groups 1, 2 and 3 respectively. Ultrastructural analysis showed differences between frozen/thawed and fresh embryos. In the former, embryonic cells were deformed and showed dilation of the intercellular and perivitelline spaces, a decrease of desmosome number in the junctional complexes, few microvilli on the apical surface of the trophectoderm and an almost total absence of pinocytotic vesicles. Most of the mitochondria showed regions containing dilation and irregularities on the cristae, which appeared electron-dense. The results obtained with Groups 2 and 3 embryos showed that the cryoprotectants employed were not effective in protecting the embryos against damage during freezing and thawing. Indeed, the ultrastructural changes observed in the Group 3 embryos explained the absence of any established pregnancies in this group of mares.
Keywords: cryoprotective agent; glycerol; propylene glycol; sucrose; animal; animal disease; cohort analysis; comparative study; cryopreservation; drug effect; embryo; embryo transfer; female; freezing; horse; methodology; physiology; prenatal development; time; ultrastructure; Animals; Cohort Studies; Cryopreservation; Cryoprotective Agents; Embryo; Embryo Transfer; Female; Freezing; Glycerol; Horses; Propylene Glycol; Sucrose; Time Factors